Human norovirus infection and the acute serum cytokine response. (22nd September 2015) - Newman, K L; Moe, C L; Kirby, A E; Flanders, W D; Parkos, C A; Leon, J S
Summary: Noroviruses (NoV) are the most common cause of epidemic gastroenteritis worldwide. The acute immune response to NoV in humans is poorly understood, hindering research on prevention and treatment. To elucidate the acute immune response and test for cytokine predictors of susceptibility to infection, serum samples from two human NoV challenge studies were tested for 16 cytokines. Subjects who became infected ( n = 26) were age-matched with subjects who remained uninfected following NoV challenge ( n = 26). Samples were tested from prechallenge and days 1-4 post-challenge. Cytokine responses were compared between infected and uninfected groups. Overall, infected individuals exhibited an elevation in T helper type 1 (Th1) and Th2 cytokines, as well as chemokines interleukin (IL)-8 and monocyte chemoattractant protein (MCP-1), compared to uninfected individuals (all P < 0·05). Most cytokines peaked on day 2 post-challenge in infected subjects, and tumour necrosis factor (TNF)-α, IL-8, and IL-10 remained elevated to day 3. The only cytokine elevated significantly among infected subjects to day 4 post-challenge was IL-10 ( P = 0·021). Prechallenge cytokine concentrations were not predictive of infection status post-challenge. There were no significant changes in serum cytokines among NoV-challenged subjects who remained uninfected. These results suggest that NoV infection elicits a Th1-type response, with some Th2 activation. Persistent elevation of IL-10 among infected subjects is consistent with activation of adaptive immune responses, such as B cell expansion, as well as down-regulation of Th1 cytokines. This study presents the first comprehensive description of the acute cytokine response to GI.1 NoV in humans.